1997
DOI: 10.1093/oxfordjournals.alcalc.a008240
|View full text |Cite
|
Sign up to set email alerts
|

Nature and Healing of Tibial Shaft Fractures in Alcohol Abusers

Abstract: Alcohol abuse is associated with an increased risk of osteopenia and fractures. Previous histomorphometric studies on iliac crest bone have found decreased bone formation and increased bone resorption in alcohol abusers but it has not been established whether alcohol abuse has any effect on the anatomical location or the healing time of tibial shaft fractures. We studied, retrospectively, 199 adult male patients hospitalized for isolated tibial shaft fracture in the city of Malmö, Sweden, between 1980 and 1990… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 21 publications
3
36
0
Order By: Relevance
“…The limited available data suggest that alcoholism does not increase the incidence of nonunions, osteonecrosis, or other complications (Nyquist et al, 1997(Nyquist et al, , 1998 but is associated with an increase in healing time for transverse fractures (Nyquist et al, 1997).…”
Section: Effects Of Alcohol Abuse On Bone Mass and Fracture Incidencementioning
confidence: 98%
“…The limited available data suggest that alcoholism does not increase the incidence of nonunions, osteonecrosis, or other complications (Nyquist et al, 1997(Nyquist et al, , 1998 but is associated with an increase in healing time for transverse fractures (Nyquist et al, 1997).…”
Section: Effects Of Alcohol Abuse On Bone Mass and Fracture Incidencementioning
confidence: 98%
“…Intoxication increases risks for both sustaining fracture injuries as well as adversely affecting the healing process. Human studies have shown that healing and recovery from fractures is adversely affected and is prolonged with higher rates of complications in patients with significant EtOH exposure (3,23,24).…”
Section: Discussionmentioning
confidence: 99%
“…Among the numerous physiological effects of alcohol exposure, it has been widely shown that alcohol interferes with bone formation and fracture healing. Patients who abuse alcohol have prolonged healing time following transverse tibial fractures (3).…”
mentioning
confidence: 99%
“…The limited available data suggest that alcoholism does not lead to an increase in the incidence of nonunions, osteonecrosis or other complications (Nyquist et al, 1997;Nyquist et al, 1998), but is associated with an increase in healing time for transverse fractures (Nyquist et al, 1997).…”
Section: Effects Of Alcohol Abuse On Bone Mass and Fracture Incidencementioning
confidence: 99%